A Review on an Opportunity to Reduce Exhaust Emission from Diesel Engine Using Exhaust Gas Recirculation - Mandalia, Hiren V. (Asian Review of Mechanical Engineering, 2015)
Internal combustion engines, plays an important role in the transportation sector and also in individual transport. Also it is a major source of manmade emissions. Presently there are many technologies are developed which are used to reduce the fuel consumption and exhaust emission from a diesel engine. In a CI engine fuel consumptions is reduced to a considerable amount, but the emission of NOx (Nitrogen Oxide) is a critical issue. This paper tries to present a review about the impact of EGR system on the exhaust emission of a CI engine. This is one of the methods which reduce the nitrogen oxide emissions of a diesel engine to a considerable level. In EGR – Exhaust Gas Recirculation method, a part of the exhaust gases is recirculated into the combustion chamber. Due to complete combustion of unburned fuel particles, there is a reduction in peak combustion temperature which in turn reduces the formation of NOX. By controlling the amount of available oxygen, which makes possibilities of reduction in the flame temperature in the combustion chamber, EGR system is effectively reduce the NOx emission from an engine.